Black rice as the emerging functional food: bioactive compounds, therapeutic potential and industrial applications - Javed, Mavra; Jawid, Jawaria; Zafar, Saira; Ahmad, Abdul Momin Rizwan; Shah, Syed Hassan Bin Usman; Farooq, Umar; Abid, Juweria (Frontiers in Nutrition, 2025)
It is now widely understood that black rice, also known as Oryza sativa L., is a functional food and a nutritional powerhouse. In the past, it was known as forbidden rice. The current analytical viewpoints on recent breakthroughs in black rice research are investigated in this review paper. Topics covered include the bioactive chemicals of black rice, its potential therapeutic applications, and its applications in the food business. The fact that black rice includes bioactive compounds that have antioxidants, cardiovascular preventative properties, and anti-diabetic effects has been proven through clinical and metabolomic research. Additionally, this study addresses recent innovations in the gluten-free sector and packaging, as well as showing how processing methods influence bioactive substances. It is anticipated that the global market for black rice would be worth USD 15.14 billion by the year 2030. This reflects the growing demand among consumers for nutrient-dense superfoods. Taking this into consideration, there is a need for additional investigation into the true potential of black rice in the food and wellness business. This is necessary to ensure that this superfood may be utilized to the fullest extent of its potential in the future.